2014
DOI: 10.1186/s13075-014-0473-5
|View full text |Cite
|
Sign up to set email alerts
|

Safety and possible effects of low-intensity resistance training associated with partial blood flow restriction in polymyositis and dermatomyositis

Abstract: IntroductionOur aim was to evaluate the safety and efficacy of a low-intensity resistance training program combined with partial blow flow restriction (BFR training) in a cohort of patients with polymyositis (PM) and dermatomyositis (DM).MethodsIn total, 13 patients with PM and DM completed a 12-week twice a week low-intensity (that is, 30% one-repetition-maximum (1RM)) resistance exercise training program combined with partial blood flow restriction (BFR). Assessments of muscle strength, physical function, qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
94
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(109 citation statements)
references
References 32 publications
7
94
0
6
Order By: Relevance
“…Studies involved individuals with knee OA41 49 50 (n=3), ligament injuries42 51 52 (n=3), sporadic inclusion body myositis53 (n=1) and older adults susceptible to sarcopenia26 27 54–64 (n=13). The average age was 58±14 years for a sample range of 10–41 participants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies involved individuals with knee OA41 49 50 (n=3), ligament injuries42 51 52 (n=3), sporadic inclusion body myositis53 (n=1) and older adults susceptible to sarcopenia26 27 54–64 (n=13). The average age was 58±14 years for a sample range of 10–41 participants.…”
Section: Resultsmentioning
confidence: 99%
“…Muscle size was assessed by examining muscle CSA,26 27 42 51–53 56 59 61–63 muscle mass,56 muscle volume,27 41 muscle thickness58 60 and fat cross-sectional area (CSA) 59. Studies that assessed physical function included tests of reaction time,54 stair climb power,41 single leg balance,54 timed stands,53 10 m walking time,54 maximum step distance,54 functional reach test,54 chair stand26 56 and the timed up and go test 26 50 53 54 56. A number of studies reported the presence or absence of any adverse events relating to BFR 41 49 53–55 57 59 63 64…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, BFR may serve as a beneficial tool for increasing muscle size and strength among those who are unable to perform high-load resistance training (i.e., clinical populations). Further support for the use of BFR in clinical populations exists, in that low-load BFR training has been shown to be a safe stimulus [25] and has been demonstrated effective at increasing muscle size and strength in elderly [26] and diseased (myositis) [27] populations, as well as those rehabilitating from injury [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…The EVO is useful for various populations as athletes, old people, or subjects with inflammatory muscle diseases, as well as, with osteoarthritis [8][9][10].…”
Section: Introductionmentioning
confidence: 99%